Rupiah weakens further: an analysis of export challenges and opportunities - Ahmad Aji Syafi'i Wibowo; Riani, Lilia Pasca (Universitas Nusantara PGRI Kediri, 2025)
Research Aim: This study aims to analyze the impact of Rupiah depreciation on Indonesia's export sector, highlighting both its risks and opportunities for trade competitiveness and economic resilience.Design/Method/Approach: The study adopts a qualitative descriptive approach using secondary data analysis from economic reports, policy briefs, and trade statistics.Research Findings: Rupiah depreciation increases import costs for raw materials and technology, raising production expenses and potentially weakening global competitiveness. It may also trigger inflation and reduce consumer purchasing power. However, a weaker currency improves export price competitiveness, boosts demand for commodities such as palm oil and coal, encourages the use of domestic raw materials, and can attract foreign investment.Theoretical Contribution/Originality: This research contributes to the discourse on exchange rate policy by emphasizing the dual nature of currency depreciation in developing economies, providing a balanced view of its macroeconomic implications.Practical/Policy Implications: Policymakers are encouraged to diversify export destinations, strengthen domestic supply chains, and enhance industrial efficiency to maximize the benefits of currency depreciation.Research Limitations: The analysis is limited to secondary data and does not include empirical modeling or case-specific data from individual exporting firms.